Music after the fall modern composition and culture since 1989 - Rutherford-Johnson, Tim (University of California Press, 2017)
By the start of the 21st century many of the foundations of postwar culture had disappeared: Europe had been rebuilt and, as the EU, had become one of the world's largest economies; the United States' claim to global dominance was threatened; and the postwar social democratic consensus was being replaced by market-led neoliberalism. Most importantly of all, the Cold War was over, and the World Wide Web had been born. 'Music After The Fall' considers contemporary musical composition against this changed backdrop, placing it in the context of globalization, digitization, and new media. Drawing on theories from the other arts, in particular art and architecture, it expands the definition of Western art music to include forms of composition, experimental music, sound art, and crossover work from across the spectrum, inside and beyond the concert hall
Previously issued in print: 2017
Keywords: Geschichte 1989-2016; Music -- 20th century -- History and criticism; Music -- 21st century -- History and criticism; Composition (Music) -- History -- 20th century; Composition (Music) -- History -- 21st century; Music -- Social aspects -- History -- 20th century; Music -- Social aspects -- History -- 21st century; Popular culture -- History -- 20th century; Popular culture -- History -- 21st century; Music and globalization; Music and technology; Politischer Wandel; Globalisierung; Neue Musik